« Ésotérique »: John Toland et le parcours historique d’un adjectif français = "Ésotérique": John Toland and the Historical Journey of a French Adjective - Fischer, Tom (Aries, 2026)
AbstractThis article traces the historical appearance of the adjective "ésotérique" in the French-speaking world. The term appeared in printed sources as early as 1721, more than a century before the first use of the word "ésotérisme" (dated 1828). This adjective was not created ex-nihilo but, drawing its roots from Greek, was introduced from England through two book reviews respectively written by the Huguenot journalist Michel de la Roche (d. 1742) and the Calvinist preacher Armand Boisbeleau de la Chapelle (1676-1746). The work criticised was none other than the Clidophorus by the Irish philosopher John Toland (1670-1722), which set out to decipher and expose the "secret doctrines" of the ancient philosophers. This transmission bias provides us with information about the original understanding of this adjective when it was introduced in France, and bears witness to the fertile cultural exchanges that were taking place in Europe at the time, even in the field of "rejected knowledge"., AbstractThis article traces the historical appearance of the adjective "ésotérique" in the French-speaking world. The term appeared in printed sources as early as 1721, more than a century before the first use of the word "ésotérisme" (dated 1828). This adjective was not created ex-nihilo but, drawing its roots from Greek, was introduced from England through two book reviews respectively written by the Huguenot journalist Michel de la Roche (d. 1742) and the Calvinist preacher Armand Boisbeleau de la Chapelle (1676-1746). The work criticised was none other than the Clidophorus by the Irish philosopher John Toland (1670-1722), which set out to decipher and expose the "secret doctrines" of the ancient philosophers. This transmission bias provides us with information about the original understanding of this adjective when it was introduced in France, and bears witness to the fertile cultural exchanges that were taking place in Europe at the time, even in the field of "rejected knowledge".